A technology comparison concerning scale dependencies of industrial furnaces. A case study of glass production. (August 2017) - Dorn, Corina; Behrend, Ralph; Uhlig, V.; Trimis, D.; Krause, H.
Abstract: Industrial furnaces are analyzed continuously to identify optimization potentials. Process data from the glass industry suggest that the size of a plant has an important influence on the specific energy consumption. This leads to incorrect results when using key performance indicators (KPIs) for comparison purposes. Therefore, the evaluation of innovative industrial technologies, as the use of microwaves, is often affected by incomplete assumptions, since economies of scale are often disregarded. A thermodynamic model for energy consumption was developed for analysing the scale dependencies on the specific energy consumption. It contains a correction factor for KPIs. This factor will be compared and validated with industrial process data from literature and databases as well as experimental data for the microwave process. The paper shows the impact of existing scale dependencies and their importance for a comprehensive technology comparison.